The effect of nitrogen in alpha-iron on ferromagnetic domain boundary movement examined by a mechanical damping method - Steward, M. J. (College of Aeronautics, 1963)
The effect of ageing below 200°C on the hysteresis loss in a-iron containing nitrogen has been investigated. The extent to which nitrogen is removed from solid solution during ageing, and the domain boundary hindrance developed, was assessed by mechanical damping, using a low-frequency inverted torsional pendulum. Nitrogen, both in solution and as the precipitated form Fe5N, was found to increase the resistance to domain boundary movement, the precipitated form being the more effective in this respect. Most of the damping changes due to ageing are developed in less than 2 hours at 150°C; a further investigation to cover this region would need to be undertaken to establish quantitative relationships.